The survival outcome of patients with metastatic colorectal cancer based on the site of metastases and the impact of molecular markers and site of primary cancer on metastatic pattern. (2nd November 2018) - Prasanna, Thiru; Karapetis, Christos S.; Roder, David; Tie, Jeanne; Padbury, Robert; Price, Timothy; Wong, Rachel; Shapiro, Jeremy; Nott, Louise; Lee, Margaret; Chua, Yu Jo; Craft, Paul; et al.
Abstract: Background: Pattern of spread in patients with metastatic colorectal cancer (mCRC) is variable and may reflect different biology in subsets of patients. This is a retrospective study to explore the outcome of patients with mCRC based on their site of metastasis at diagnosis and to explore the association between tumor characteristics [KRAS/RAS, BRAF, mismatch repair (MMR) status, site of primary] and the site of metastasis. Methods: Patients from two Australian databases were divided into six groups based on site of metastasis at time of diagnosis of metastatic disease; lung-only, liver-only, lymph node-only or any patients with brain, bone or peritoneal metastases. Primary endpoint was overall survival (OS) of each cohort compared with the rest of the population. A Mantel–Haenszel chi-squared test used to explore the association between site of metastasis and selected tumor characteristics. Results: Five thousand nine hundred and sixty-seven patients were included. In a univariate analysis, median OS was significantly higher when metastases were limited to lung or liver and shorter for those with brain, bone or peritoneal metastases ( p  < .001) in both datasets. BRAF mutation was strongly associated with peritoneal metastases (relative risk = 1.8, p  < .001) with lower incidence of lung (RR = 0.3, p  = .004) and liver (RR = 0.7, p  = .005) limited metastases. Lung-only metastases were more frequent with KRAS/RAS mutation (RR = 1.4, p  = .007). Left colon tumors were associated with bone (RR = 1.6, p  < .001) and lung-only metastases (RR = 2.3, p  = .001) while peritoneal spread was less frequent compared with right colon tumors (RR = 0.6, p  < .001). Rectal cancer was associated with brain, bone and lung metastases (RR = 1.7; p  = .002, 1.7; p  < .001, 2.0; p  < .001). Liver-only metastases were less frequent in deficient MMR tumors (RR = 0.7, p  = .01). Conclusion: Survival duration with mCRC is related to the site of metastases with lung limited disease showing a more favorable survival outcome compared to other single metastatic site disease. The BRAF mutation and primary rectal cancer were associated with poor prognostic metastatic sites.